Effect of Cognitive Behavioral Therapy for Anxiety Disorders on Quality of Life: A Meta-Analysis - Hofmann, Stefan G. (2014)
OBJECTIVE: Although cognitive-behavioral therapy is effective for treating anxiety disorders, little is known about its effect on quality of life. To conduct a meta-analysis of cognitive-behavioral therapy for anxiety disorders on quality of life, we searched for relevant studies in PubMed, PsycINFO and the Cochrane Library, and conducted manual searches. METHOD: The search identified 44 studies that included 59 CBT trials, totaling 3,326 participants receiving cognitive-behavioral therapy for anxiety disorders. We estimated the controlled and within-group random effects of the treatment changes on quality of life. RESULTS: The pre-post within-group and controlled effect sizes were moderately strong, Hedges’ g = 0.54 and Hedges’ g = 0.56, respectively. Improvements were greater for physical and psychological domains of quality of life than for environmental and social domains. The overall effect sizes decreased with publication year and increased with treatment duration. Face-to-face treatments delivered individually and in groups produced significantly higher effect sizes than internet-delivered treatments. CONCLUSION: Cognitive-behavioral therapy for anxiety disorders is moderately effective for improving quality of life, especially in physical and psychological domains. Internet-delivered treatments are less effective in improving quality of life than face-to-face treatments.